SAMPAH DAN PENINGKATAN EKONOMI MASYARAKAT DESA: TINJAUAN KOMUNIKASI PEMBERDAYAAN PEMUDA - Iswan Afandi; Didi Rukmana; Eymal Mallino (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
This study aims to: (1) identify and analyze in-depth the process of community empowerment by youth in Salassae Village, Bulukumba Regency through a waste bank program (2) to analyze in-depth the communicative actions of youth in the empowerment process. Research using qualitative methods of data collection is done by in-depth interviews, observation, and documentation. Data analysis was carried out with an interactive analysis model. This study resulted in several conclusions, namely (1) The empowerment process in the village of Salassae was initially pioneered by youth by forming a community called KASIMPADA, based on awareness of environmental conditions that would be threatened by waste, which increased in volume every day, the KASIMPADA Management agreed to establish an institution that specifically handles waste in rural areas, especially in the village of salassae. (2) youth communicative actions in the empowerment process, marked by interactions based on awareness and willingness to communicate in an empathic and ethical way.